Development of a methodology for the estimation of the dynamic evolution of the flood-related hydrological behavior of periurban catchments under post-fire conditions - Papathanasiou, Chrysoula (Σχολή Πολιτικών Μηχανικών, 2018)
The primary aim of this dissertation is the development of a methodological framework to theoretically estimate the dynamic evolution of hydrological parameters that affect flood risk as a function of time, following the occurrence of forest fires. The research focuses on flood risk assessment under post-fire conditions for Mediterranean periurban catchments. To this end, a methodological framework to theoretically estimate the dynamic evolution of hydrological parameters that affect flood risk as a function of time, following the occurrence of forest fires has been developed. For this research the term “hydrological recovery” was introduced for the first time in international literature in order to describe the (post-fire) stage when the hydrological response of a burnt catchment has recovered, for all practical (hydrological response) purposes, to its pre-fire state. It is suggested that hydrological recovery may occur earlier than (a more complete) “environmental recovery”, which is achieved when the catchment’s natural reforestation and ecosystem rebalance occur – a process that often takes several years (if at all) after a major fire event. First, the impact of forest fires on a catchment has been examined from a spatiotemporal perspective. This impact depends strongly on fire extent and Fire Severity. Time periods of variable duration and different hydrological impact, directly associated with the status of vegetation regrowth, were identified within each severity class. Then, initial conditions are examined in terms of soil moisture. Curve Number (CN), Initial Abstraction (IA), Standard Lag (TP), Peaking Coefficient (CP) and Muskingum K coefficient were selected for this research and the change in their values for different initial conditions has been quantified. The time interval between the occurrence of a fire event and the analyzed flood events was also taken into consideration. Hence, a set of equations was developed to express the post-fire evolution in time of each examined hydrological parameter. The study area is Rafina catchment, a typical Mediterranean periurban area in Eastern Attica region, particularly prone to floods and forest fires. The application of the equations yielded the final values of the hydrological parameters, used for simulations of historic floods. For all examined flood events the simulated peak flows, runoff volumes and times to peak match well to the corresponding values derived from observed datasets, when available. A detailed sensitivity analysis that verifies the efficiency of the proposed methodology was also performed and representative flood maps were produced for the study area. It is concluded that the post-fire impact is very intense during the first post-fire period, while it is sharply decreasing with time, until hydrological recovery occurs and the post-fire hydrological footprint vanishes. This impact is not the same on all examined hydrological parameters, while the calibration of all 5 parameters yields optimum simulations. Finally, it is concluded that the incorporation of the proposed methodology in a hydrological model yields accurate and representative simulations.